(untitled) (American Journal of Technology and Applied Sciences, 2025)
The physical basis of electromechanical transducers is based on the force interaction of the measured current with auxiliary magnetic fields or ferromagnetic masses. They have a number of advantages, such as the simplicity of their construction, high reliability, absolute autonomy, the implementation of multiple limits, the possibility of measuring direct, variable and impulse currents.